Organoleptic Characteristics Of Cow Skin Cracker With Variety Of Skin Types And Souring Time - Ibrahim, Anita Mustika; Hafid, Harapin; Bain, Ali (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2021)
Skin crackers are snacks which made from cattle skin. In order to get a good quality of skin crackers, the immersion process is carried out in a mixture of whiting solution and pineapple skin extract. This study aimed to evaluate the organoleptic characteristics of cow skin crackers with different types of skin and soaking time. The material used in this study is cow leather, whiting and pineapple skin. The method used is a completely randomized design factorial pattern with 3 x 3 and 4 times repetition. Factor A is the type of skin part (head, foot and neck) and factor B is difference of immersion time (24, 48, 72 and 96 hours). Research variables included color, aroma, taste, joy, crispness and acceptance of the panelists. The data obtained were analyzed using SPSS 16.0 and the smallest real difference test (LSD). The results showed that the interaction between the type of skin and immersion time did not significantly influence (P> 0.05) on color, aroma, taste, crispness, panelist acceptance and preference. Independent skin immersion time significantly influence (P <0.05) on color, aroma, taste, crispness, panelist acceptance and preference. The best treatment is obtained at 96 hours of immersion time.